New combinations in Pleradenophora (Euphorbiaceae s.s.) - de Melo, André Laurênio; Esser, Hans-Joachim; de Sales, Margareth Ferreira (Phytotaxa, 2013)
A nomenclatural update is presented for the (hitherto monotypic) genus Pleradenophora. New combinations are presented for Pleradenophora bilocularis, P. lottiae, P. membranifolia, P. tikalana and P. tuerckheimiana (based on Sebastiania bilocularis, S. lottiae, S. membranifolia, S. tikalana and Sapium tuerckheimianum), and four new synonyms are proposed. A key to the species is provided. The genus currently comprises five species, distributed from theUnited States toBolivia, with the highest diversity inMexico andGuatemala.